Grandmother-inclusive intergenerational approaches: the missing piece of the puzzle for ending FGM/C by 2030? - Newman, Anneke (Frontiers in Sociology, 2023)
This brief argues that 'grandmother-exclusionary bias' - or the side-lining of female elders as change agents within FGM/C programmes -represents a major obstacle to eradication of these practices. Grandmother-exclusionary bias is prevalent within FGM/C policy and programming. Yet, it goes against evidence of the extensive authority and decision-making roles that grandmothers wield in relation to FGM/C in sub-Saharan Africa, and insights from systems theory and meta-evaluations of FGM/C eradication efforts which stress that sustained change requires engaging those who wield authority over gender and social norms. We use postcolonial and decolonial theory to explain the assumptions about grandmothers which underpin grandmother-exclusionary bias. Finally, we provide recommendations for designing grandmother-inclusive, intergenerational community-led programmes based on a strategy empirically proven to shift social norms underpinning FGM/C.